Feeding preference and feeding activity pattern under culture conditions on Holothuria Scabra juveniles. - Dolendo, Jeanne Lee De Jose (2013.)
Algal diets namely Sargassum, spirulina and Navicula were offered simultaneously to early settled sea cucumber juveniles of Holothuria scabra (2-5 mm body length) in a 48-hour choice experiment run 3 times to determine its feeding preference. H. scabra juveniles showed significantly higher preference towards Sargassum against both Navicula and Spirulina diets (Friedman's Two Way Analysis of Variance (ANOVA) by Ranks, p<0.05) based on mean number of actively feeding juveniles in Sargassum over time and percentage grazed of total area of a food item. The feeding activity pattern of H. scabra juveniles fed with prefer diet (Sargassum) was then assessed in treatments with and without substrate. Hourly observations for 48 hours showed that H. scabra feed more actively when without substrate. Daytime/light and night time/dark cycle did not seem to influence the feeding activity pattern of early settled H. scabra juveniles as feeding appeared to be continuous.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Holothuria Scabra -- Feeding Preference; Holothuria Scabra -- Feeding Patterns